Donation and organ transplantation in public opinion of Russians - . Yuri Levada Analytical Center (Трансплантология (Москва), 2016)
This article is a part of a public report of the survey carried out by the Levada-Center, dedicated to the study of the problems of organ donation in Russia. On the basis of a nationwide survey of public opinion the author analyzes views and positions of Russians in relation to organ donation.